An integrated tool to support sustainable toy design and manufacture. Issue 1 (1st January 2017) - Shin, Kei Lok Felix; Colwill, James
Abstract: Whilst the importance of considering the positive societal benefits of a product, in addition to other social, economic and environmental factors, has received wider recognition, its definition, concept, and integration into product design are not so well developed and studied. A literature review on sustainable design identified the potential of Social Life-Cycle Assessment as a tool to measure societal benefits of products; however further analysis of sustainable assessment methods highlighted the lack of a coherent definition and method for achieving this. This paper presents a framework for including societal benefits within a product portfolio management process and a prototype tool which aims to support the implementation of the framework within the toy industry, specifically on the societal benefit assessment of the products during the first stage. Finally a simulated case study of three toys is used to exemplify the intended application of this tool and to support the concluding discussions.